POI09 Trends in BK and JC polyomavirus and relationship to CD4+/CD8+ ratio in patients with relapsing remitting multiple sclerosis on natalizumab therapy. Issue 11 (22nd October 2010) - Molloy, A; Kinsella, K; Turbridy, N; Hutchinson, M; Duggan, M; De Gascun, C F; Lonergan, R; Stack, J; Hall, W
Abstract : Natalizumab reduces clinical relapses and the risk of sustained progression of disability in patients with relapsing remitting multiple sclerosis (RR MS). It has been associated with the development of progressive multifocal leucoencephalopathy, a rare demyelinating disease caused by JC virus. BK virus is a related polyomavirus known to cause morbidity in the immunocompromised host. Studies in the HIV population have linked BK viruria with immunodeficiency as evidenced by depressed CD4+ counts. We evaluated the relationship between the prevalence of JC and BK in MS patients receiving natalizumab and the degree of immunosuppression by sampling serum and urine specimens at baseline and at 3-monthly intervals. This is an ongoing prospective, longitudinal study that started in January 2007. A total of 86 subjects with active RRMS received natalizumab in our Department. We found no significant relationship between duration of natalizumab therapy and activation of JC virus. The risk of developing BK viruria, however, increased over time with the number of doses received. No significant reductions in CD4+ counts or in CD4+/CD8+ ratios were noted. These findings indicate that while there is a link between natalizumab and BK activation no significant immunosuppressive effect was observed. Further studies on the implications of BK virus in MS remain to be done but these results may have consequences for this patient group in terms of development of infection-related adverse effects.